Investoinnit Suomessa: Kehitys ja kansainvälinen vertailu - Ville Kaitila; Pekka Ylä-Anttila (The Research Institute of the Finnish Economy (ETLA), 2012)
– The report looks at investment activity in Finland by industries and types of investment, and makes international comparisons. Investment rate (fixed investment in relation to GDP) fell in Finland in the early 1990s from an internationally high level to the average West European rate. Among key factors behind the structural change were opening up of the economy and an increase in competition. The economy transformed itself from investment-driven economy to a more innovation-driven one. The use of capital became more efficient. During the global financial and economic crisis in 2008-10 the investment rate declined in Finland as it did in most other developed countries. There are, however, some country-specific features in the Finnish case. Investment in manufacturing fell dramatically, by almost 40%, i.e. clearly more than in other EU countries. Furthermore, over the first decade of the 21st century investment in machinery and equipment has been at a substantially lower level (in relation to GDP) than in most other West European countries. On the other hand, construction investment has been relatively high in international comparison. Investments in intangible assets have steadily increased in all highly developed countries, including Finland. They have become an important source of economic growth and structural change. In Finland especially R&D expenditures have been high but their growth has stagnated. The future of R&D depends very much on the structural transformation of the ICT sector, since the sector's share in Finland's total private R&D expenditure is well above 50%.
Keywords: E22; F21; O38; 330; investment; capital; research and development; FDI; Investition; Forschungskosten; Direktinvestition; Finnland